The Influence Of Training And Work Environment On Employee Performance (Case Study: Tax Inspector at the Directorate General of Taxes) - Maulia Githa Ustadztama; Kasful Anwar; Burhanudin (Journal of Entrepreneur and Business, 2024)
There are many factors that can influence employees in an organization. The aim of this research is to find out how training and the work environment influence employee performance with competency as an intervening variable. The research method uses a quantitative approach with a questionnaire instrument, purposive sampling data collection techniques with 60 respondents, and Structural Equation Modeling (SEM) analysis methods. Based on the results of this research, it confirms: First, based on the results of this research, it confirms that training has a positive effect on employee performance. Statistical test results show that 65% of employee performance is influenced by training. Of the several indicator variables studied, it shows that the instructor's ability to provide training is the most important factor, followed by the training material factor. From the performance variables, it can be noted that achievement indicators are the strongest factor in employee performance, followed by employee behavior and characteristics. Second, the results of this research show that the work environment has a positive effect on employee performance. Statistical test results show that 46% of employee performance is influenced by the work environment. Of the several indicators studied, the influence of organizational support is the most important factor in the organizational environment, then peer relationships or support and the influence of superiors. Third, the results of this research note that employee competency has a positive influence on employee performance. Statistical test results show that 48% of employee performance is influenced by employee competency. Of the several indicators studied, employee skills/expertise are the most important factors in the competency variable, as are employee self-concept and attitudes. These three factors will have an important influence on employee performance. Keywords: Training, Work Environment, Employee Performance